New results on path-decompositions and their down-links - Benini A.,; Giuzzi L.,; Pasotti A., (Utilitas Mathematica, 2013)
In [3] the concept of down-link from a(Kv,Γ)-design B to a(Kn,Γ')-design B' has been introduced. In the present paper the spectrum problems for Γ' = P4 are studied. General results on the existence of path-decompositions and embeddings between pathdecompositions playing a fundamental role for the construction of down-links are also presented.